The Moderating Role of Firm Values in ESG Disclosure: An Integrated Signaling and Legitimacy Theory - MARISTIANA AYU (FEB - Universitas Lampung, 2026)
Environmental, Social, and Governance (ESG) disclosure is crucial for enhancing investor confidence through sustainable business practices. However, not all high-value performance firms in Indonesia apply or complete ESG disclosure. This study analyzes the moderating role of Firm Value in the effect of ESG disclosure on Stock Liquidity. It also examines the direct effect of Firm Value on Stock Liquidity. The study uses data from LQ 45 companies on the Indonesia Stock Exchange (2020-2024) and a moderated regression model. The results show that Firm Value strengthens the positive effect of ESG disclosure on Stock Liquidity. ESG disclosure and Firm Value also directly affect Stock Liquidity. This finding implies that high-value companies receive a more favorable market response to ESG disclosure. Strong Firm Values can increase investor attractiveness and company Stock Liquidity by extending Signaling theory integrated with Legitimacy theory.